KONSEP TRI HITA KARANA DALAM SUBAK - Ika Nopitasari, Ni Putu; Putrawan, Suatra (Kertha Desa, 2013)
Tri Hita Karana is a basic concept that have been applied in the Baliness people life. This concept is commonly as a base in forming an organization, one of them is the Subak organization. The Subak is a watering system or irrigation system in Bali, but in implementation of this system have been found an organization based on its members in handle their rice field. Existence of Tri Hita Karana concept in the Subak have arised a question how important the Tri Hita Karana concept in the Subak in Bali. Through this study of normative law will be analyzed sources that have correlation with concept of Tri Hita Karana in the Subak, in order to find an answer for the problem. The conclusion from analysis of existing sources that concept of Tri Hita Karana have important role in the Subak and its organization because this concept instruct to keep balance between the God, human and environment.
Keywords: Concept, Tri Hita Karana, Subak